A Comparative Review of Shoot Cutting Techniques for the Propagation of Ornamental Plants: Effectiveness and Determining Factors - Puji Ramadhani; Violita (Microbiotech, 2026)
Abstract The demand for high-quality ornamental plants that are genetically uniform continues to increase, driving the need for efficient and stable propagation methods. Stem cuttings are one of the most widely used vegetative propagation methods due to their ease and ability to maintain the superior traits of the parent plant. However, its success depends heavily on various internal and external factors, such as cutting position, tissue age, type of growing medium, application of plant growth regulators (PGRs), and environmental conditions. This study was conducted using a literature review method, analyzing twelve relevant national and international scientific articles, with the aim of evaluating the effectiveness of the stem cutting technique and identifying the main factors influencing its success. The results of the study indicate that the use of auxin-type GRPs (IBA and NAA) can enhance root initiation in various ornamental plant species, while organic growing media such as rice husks and leaf mold support root growth and photosynthetic efficiency. Responses to cutting position and the physiological condition of the parent plant also vary among species. Additionally, environmental control factors such as temperature, humidity, and light further enhance the effectiveness of the treatment. Therefore, the application of integrated and species-specific strategies is key to achieving optimal, efficient, and sustainable vegetative propagation results in ornamental plant cultivation. Key words Cuttings, ornamental plants, growing medium, vegetative propagation, rooting hormone (IBA/NAA) Abstrak Permintaan terhadap tanaman hias berkualitas tinggi yang seragam secara genetik terus meningkat, mendorong perlunya metode perbanyakan yang efisien dan stabil. Teknik stek pucuk merupakan salah satu metode perbanyakan vegetatif yang paling banyak diterapkan karena kemudahannya serta kemampuannya mempertahankan sifat unggul tanaman induk. Namun, keberhasilannya sangat bergantung pada berbagai faktor internal dan eksternal, seperti posisi stek, umur jaringan, jenis media tanam, pemberian zat pengatur tumbuh (ZPT), dan kondisi lingkungan. Penelitian ini dilakukan melalui metode studi literatur (literature review) terhadap dua belas artikel ilmiah nasional dan internasional yang relevan, dengan tujuan mengevaluasi efektivitas teknik stek pucuk serta mengidentifikasi faktor-faktor utama yang memengaruhi keberhasilannya. Hasil kajian menunjukkan bahwa penggunaan ZPT jenis auksin (IBA dan NAA) mampu meningkatkan inisiasi akar pada berbagai spesies tanaman hias, sementara media tanam berbahan organik seperti sekam padi dan leaf mold mendukung pertumbuhan akar dan efisiensi fotosintetik. Respons terhadap posisi stek dan kondisi fisiologis tanaman induk juga bervariasi antar spesies. Selain itu, pengendalian lingkungan tumbuh seperti suhu, kelembaban, dan cahaya turut memperkuat efektivitas perlakuan. Oleh karena itu, penerapan strategi yang terintegrasi dan spesifik spesies menjadi kunci untuk memperoleh hasil perbanyakan vegetatif yang optimal, efisien, dan berkelanjutan dalam budidaya tanaman hias. Kata kunci Stek pucuk, tanaman hias, media tanam, vegetative propagation, rooting hormone (IBA/NAA)